Development of a Prototype Sports Physics Module for Physics Students at Universitas Negeri Makassar - Primadi, Muhamad Baidhowi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This study aims to develop a prototype sports physics module that can be used by physics students to connect physics theory with its application in sports. The module is designed with an approach based on physics theories relevant to sports concepts, such as Newton’s laws of motion, kinetic energy, frictional force, and momentum. The development process follows a research and development (R&D) methodology, which includes the stages of needs analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, and questionnaires, involving physics students selected through purposive sampling.The results indicate that this module not only enhances students' understanding of physics concepts but also strengthens their perception of the relevance of physics in sports. A limited trial involving 20 students showed an 80% improvement in material comprehension, as measured through pretest and posttest assessments. Additionally, the module was evaluated as effective by students and expert validators, with an average feasibility score of 86%. This study makes a significant contribution to the development of more contextual and applicative physics learning, especially for physics students at the university level.